Pentingnya Evaluasi Pembelajaran Bagi Guru Pendidikan Agama Buddha dan Budi Pekerti di Kelas IX A SMP Metta Maitreya - Yadi Sutikno; Mariani Mariani; Neli Neli (STAB Maitreyawira, 2024)
Based on the results of the initial observations above, it was found that teachers need to improve their learning evaluations and it is important to carry out research on learning evaluations. Based on these observations, research will be carried out regarding the importance of learning evaluation for teachers of Buddhism and Character education in class IX A of Metta Maitreya Junior High School. This study uses a qualitative method. The time for carrying out this research is January to March 2024. The research location is Metta Maitreya Junior High School which is located on Jalan Tuanku Tambusai, Puri Nangka Sari Complex, Pekanbaru. The data sources come from the Principal of Metta Maitreya Junior High School, two Buddhist and Character Education teachers, two students, and parents. Data collection techniques through observation, interviews and documentation. The results of this research are 1. to find out whether the assessment carried out by the teacher is systematic, continuous and comprehensive for students to obtain information about students' abilities (learning outcomes) in achieving learning goals, 2. can increase teacher creativity because when creating questions tests, teachers think creatively to produce problems or questions that must be answered by students, 3. Learning evaluations can make teachers self-reflect on whether their learning methods need to be improved or not, 4. can improve the quality of teacher learning in the classroom.